ESL student teachers beliefs about learning Arabic as a foreign language - Jusoh, Zailani; Abdullah, Liza (AESS Publications, 2020)
Learning a foreign language is a daunting task for many especially adult learners. This is because their motivation to learn the languages varies from one individual to another. Some do it to fulfill graduation requirement from the institution they are studying in while others, for fun. Thus, owing to these differences, understanding their attitude and beliefs about the language they take up is important as the belief affects language learning performance. This paper is written to investigate the beliefs of student teachers majoring in Teaching English as a Second Language (TESL) about learning Arabic as a foreign/third language. The respondents were enrolled in Arabic as foreign language class to meet the graduation requirement. Data for the study were collected using BALLI, an instrument to measure students’ beliefs about language learning. As this is a descriptive study, the data gathered were analysed using percentage. In general, respondents held positive beliefs about learning Arabic despite having some unrealistic beliefs about the language. The findings have a number of contributions both pedagogically and practically. One pedagogical implication the study contributes is with regards to the needs to inculcate realistic beliefs among students in learning Arabic as a foreign language.